The Influence of Service Quality, Customer Satisfaction and Company Image on Customer Loyalty of Bank Mandiri Kcp Bendungan Hilir, Central Jakarta - Naraswati, Atika; Hardini, Resti; Digdowiseiso, Kumba (Equivalent: Jurnal Ilmiah Sosial Teknik, 2024)
This study aims to analyze the effect of service quality, customer satisfaction and corporate image on customer loyalty at Bank Mandiri KCP Bendungan Hilir Central Jakarta, where the service quality provided, customer satisfaction is priority, as well as corporate image that can give a positive impression to customers will strengthen customer loyalty at Bank Mandiri KCP Bendungan Hilir Central Jakarta. The results used data primary in the form of the questionnaire. The technique of sampling using nonprobability sampling design using purposive sampling. The population of this study is the customer Bank Mandiri KCP Bendungan Hilir with a total sample is 100 people. The methods used is double linear regression that shows that there is the effect of a positive and significant between service quality, customer satisfaction and corporate image with customer loyalty.